Analysis of Factors Influencing the Application of Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP) in Cooperative Financial Reporting in Bogor City - Yuppy Triwidatin; Abdullah (International Journal of Economics, Business Management and Accounting (IJEBMA), 2019)
Study This aim For know influencing factors _ application standard accountancy finance entity without accountability public . factors the is level education part finance cooperative , age effort , socialization of SAK ETAP and understanding accounting . Population palace researcher This is whole cooperative active in the city of Bogor. Whereas For sample study are 83 cooperatives use purposive sampling method . Data analysis technique used in study This is analysis multiple linear regression . Research results show that level education part finance cooperative , age effort , socialization of SAK ETAP and understanding accountancy influential positive and significant in a manner simultaneous to application of SAK ETAP. For level education part finance cooperative influential positive in a manner Partial to application of SAK ETAP, meanwhile age business No influential positive and significant in a manner Partial to implementation of SAK ETAP, socialization of SAK ETAP has an effect positive and significant in a manner Partial to implementation of SAK ETAP and understanding accountancy influential positive and significant in a manner Partial  to application of SAK ETAP